Islamic Family Education as the Foundation for Children's Character Formation - Masruatus Saadah (CV Edujavare Publishing, 2026)
Islamic family education plays a fundamental role in shaping children’s character development amid contemporary social and technological challenges. This study aims to analyze the role of Islamic family education as the foundation for children’s moral, spiritual, emotional, and social formation within the family environment. The study employs a participatory educational and qualitative approach through community service activities involving parents, educators, and community members. Data were obtained through observations, interactive discussions, parenting workshops, and mentoring activities related to Islamic parenting practices. The findings indicate that Islamic family education significantly contributes to the development of positive character traits such as honesty, discipline, empathy, responsibility, respect, and emotional resilience among children. Religious habituation, positive communication, parental role modeling, and consistent moral guidance were identified as the primary factors supporting effective character formation. However, modern challenges such as digital media exposure, limited family interaction time, and globalization increasingly influence children’s behavior and weaken parental authority. Therefore, adaptive parenting strategies integrating Islamic values with contemporary educational approaches are necessary to strengthen children’s character in the modern era. The study also reveals that collaboration between family, school, and community environments enhances the effectiveness of Islamic character education. Overall, Islamic family education remains highly relevant in fostering morally responsible, spiritually grounded, and socially conscious future generations. The study contributes to the discourse on Islamic education by emphasizing the importance of strengthening family-based moral education as a response to current societal challenges.